2019
DOI: 10.30994/sjik.v8i2.213
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Murottal Al-Qur’an Therapy by Surah Ar-Rahman toward Anxiety of Crhonic Kidney Disease (CKD) which is being Hemodialysis at Gambiran Hospital Kediri

Abstract: Chronic kidney disease is a decrease in the function of kidney which is caused by a process of irreversible damage, thus requiring hemodialysis therapy as a replacement therapy for the function of kidney. Hemodialysis patients often experience psychosocial problem. It is an anxiety. This research aims to analyze the effectiveness of Murottal Al-Qur'an therapy by surah Ar-Rahman toward anxiety of Chronic Kidney Disease (CKD) which is being hemodialysis. The research was conducted at Gambiran Hospital Kediri. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Positive responses were seen in respondents who experienced chronic kidney disease who underwent hemodialysis, such as looking calm while closing their eyes and enjoying the sound of surah Ar -Rahman. This shows that the respondent is in a pleasant condition and has good hearing and anxiety that was previously very severe can be reduced (Suhita, Arini and Kardjati, 2019).…”
Section: Qur'an On Reducing Anxietymentioning
confidence: 88%
See 1 more Smart Citation
“…Positive responses were seen in respondents who experienced chronic kidney disease who underwent hemodialysis, such as looking calm while closing their eyes and enjoying the sound of surah Ar -Rahman. This shows that the respondent is in a pleasant condition and has good hearing and anxiety that was previously very severe can be reduced (Suhita, Arini and Kardjati, 2019).…”
Section: Qur'an On Reducing Anxietymentioning
confidence: 88%
“…This anxiety can be reduced when the patient is not nervous, does not feel tense and restless, the patient feels comfortable, the patient does not ask any more questions about the hemodialysis process and the patient does not feel cold sweat (Suhita, Arini and Kardjati, 2019) . Reducing anxiety with stimulation can increase the natural release of endorphins and balance brain waves so that listeners get a positive response in the form of relaxation or calm and comfort and have an effect on reducing perceived anxiety (Yudha, Ludiana Ludiana and Sari, 2021).…”
Section: Qur'an On Reducing Anxietymentioning
confidence: 99%
“…In four small randomized studies, including hemodialysis patients, the cognitive behavioral therapy group considerably improved their depression [ 2 , 9 , 11 , 12 ]. The patients who underwent cognitive behavioral therapy experienced improvements in their sleep issues, general psychological health, and decreased oxidative stress and inflammation [ 24 , 25 ]. Cognitive behavioral therapy, along with physical activity, might help dialysis patients’ anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the patient is comfortable, focused, and able to control their anxiety. Listening to the calming murottal might stimulate the brain to release more endorphins, which reduces perceived anxiety and normalizes brainwaves [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation